2017
DOI: 10.1016/j.catena.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Genesis and evolution of regoliths: Evidence from trace and major elements and Sr-Nd-Pb-U isotopes

Abstract: 15Regoliths encompass different materials from the fresh bedrock to the top of the organic 16 horizons. The occurrence and evolution of these materials are determined by deposition, 17 erosion and weathering processes that are specific for each region. The origin and interaction 18 of the regolith layers are still important issues in the study of critical zone functioning. 19Studies that attempt to understand the processes responsible for the structure and the 20 evolution of regoliths often focus either on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 68 publications
(7 reference statements)
3
43
0
Order By: Relevance
“…Regarding the distribution of U concentration on the depth of the soil profile, it can be observed that with increase of the depth the U concentration from soil decreases, as in the case of Pb. The results agree with Moragues-Quiroga et al [33] 0.03 mg/kg (U); and significantly lower than those obtained by Saat et al [34] 2.21 mg/kg (U).…”
Section: Heavy Metals Content From Merlot Soil Samplessupporting
confidence: 89%
“…Regarding the distribution of U concentration on the depth of the soil profile, it can be observed that with increase of the depth the U concentration from soil decreases, as in the case of Pb. The results agree with Moragues-Quiroga et al [33] 0.03 mg/kg (U); and significantly lower than those obtained by Saat et al [34] 2.21 mg/kg (U).…”
Section: Heavy Metals Content From Merlot Soil Samplessupporting
confidence: 89%
“…In our study area, Juilleret, Iffly, Hoffmann, and Hissler () have recently shown the potential for soil surveys to add useful and complementary data to existing geological maps. Recent research in the schistous Weierbach catchment by Martínez‐Carreras et al () has revealed the importance of two distinct landscape entities (i.e., plateaus and hillslopes) and their subsequent links to bedrock weathering and soil type (Moragues‐Quiroga et al, ). Their seasonal interplay relative to streamflow generation imparts single‐ or double‐peaked (delayed) storm hydrographs.…”
Section: Discussionmentioning
confidence: 99%
“…1). The area is characterized by shallow soils overlying periglacial deposit layers and Devonian slate bedrock (Juilleret et al, 2011; Moragues‐Quiroga et al, 2017). Catchment runoff shows distinct differences between dry and wet catchment states, with single‐peak hydrographs during dry and double‐peak hydrographs (Martínez‐Carreras et al, 2016) under wet conditions.…”
Section: Study Site and Previous Workmentioning
confidence: 99%